2005
DOI: 10.1207/s15327914nc5202_11
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of c-Jun N-terminal Kinase in G2/M Arrest and Caspase-Mediated Apoptosis Induced by Sulforaphane in DU145 Prostate Cancer Cells

Abstract: Sulforaphane (SFN) is a major isothiocyanate compound in cruciferous vegetables such as broccoli, cauliflower, and Brussels sprouts. Preclinical animal models have recently shown that SFN and other isothiocyanates may be useful for prostrate cancer (PCa) chemoprevention. In this study we used a DU145 human PCa cell culture model to investigate the role of protein kinase signaling pathway(s) in SFN-induced cell cycle arrest and apoptosis and whether another chemopreventive agent selenium enhances the apoptosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
82
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(95 citation statements)
references
References 30 publications
10
82
0
1
Order By: Relevance
“…On the other hand, the SFN-mediated G 2 -M phase cell cycle arrest is rapid and evident as early as 4 h posttreatment. The G 2 -M phase cell cycle arrest by SFN treatment at concentrations within the range used in the present study has also been observed in other cellular systems including HT29 human colon cancer cell line (15), F3II mouse sarcomatoid mammary carcinoma cell line (17), PC-3 and DU145 human prostate cancer cells (19,20), and human benign prostate hyperplasia epithelial cell line BPH-1 (23). In contrast, previous studies by Chiao et al (46) have documented a G 1 phase cell cycle arrest in LNCaP cells following a 24-h exposure to 3 and 9 Amol/L SFN.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…On the other hand, the SFN-mediated G 2 -M phase cell cycle arrest is rapid and evident as early as 4 h posttreatment. The G 2 -M phase cell cycle arrest by SFN treatment at concentrations within the range used in the present study has also been observed in other cellular systems including HT29 human colon cancer cell line (15), F3II mouse sarcomatoid mammary carcinoma cell line (17), PC-3 and DU145 human prostate cancer cells (19,20), and human benign prostate hyperplasia epithelial cell line BPH-1 (23). In contrast, previous studies by Chiao et al (46) have documented a G 1 phase cell cycle arrest in LNCaP cells following a 24-h exposure to 3 and 9 Amol/L SFN.…”
Section: Discussionsupporting
confidence: 72%
“…Previous studies have revealed that SFN treatment causes G 2 -M phase cell cycle arrest in different cells including p53-deficient PC-3 cells (15,19,20,23). We also found that the SFN-induced G 2 -M phase cell cycle arrest in PC-3 cells is caused by checkpoint kinase 2 (Chk2) -mediated phosphorylation of Cdc25C leading to its sequestration in the cytosol (19).…”
Section: Introductionmentioning
confidence: 53%
“…In addition, the involvement of JNK in the regulation of cell cycle progression has also been noted in previous reports; JNK mediates G 2 /M arrest induced by sulforaphane (Cho et al, 2005) and diallyl trisulfide (Antosiewicz et al, 2006) in human prostate cancer cells, and by thiazolidin compounds in human non-small-cell lung and colon cancer cells (Teraishi et al, 2005). It is interesting to note that glial cell line-derived neurotropic factor induces G 2 /M cell cycle delay via the Rac1/JNK pathway (Fukuda et al, 2005).…”
Section: Dual Effect Of Plitidepsin In Human Melanoma Cells Discussionsupporting
confidence: 70%
“…It has been shown that Akt regulates cell cycle by controlling of cyclins and CDK inhibitors (49)(50)(51)(52). In addition, JNK is involved in cell-cycle progression and mediates G 2 -M phase cell-cycle arrest in different tumor cells (53)(54)(55)(56)(57)(58). As both, decreased phosphorylation of Akt and increased phosphorylation of JNK are evident after treatment with 1, these signaling cascades may be responsible for the observed G 2 -M arrest upon treatment.…”
Section: Discussionmentioning
confidence: 98%